2015
DOI: 10.1016/j.jcct.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of coronary calcium and stent image subtraction using 320-detector row CT angiography

Abstract: Background The reader confidence and diagnostic accuracy of coronary CT angiography (CCTA) can be compromised by the presence of calcified plaques and stents causing blooming artifacts. Compared to conventional invasive coronary angiography(ICA), this may cause an overestimation of stenosis severity leading to false positive results. In a pilot study we tested the feasibility of a new coronary calcium image subtraction algorithm in relation to reader confidence and diagnostic accuracy. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…However, both CT and MRI have drawbacks, like (high) doses of ionizing radiation, nephrotoxic contrast agents, impaired visualization of stenosis in stents and highly calcified vessels for CT and limited spatial and temporal resolution, limited patient access and restrictions for certain implants and medical devices for MRI. Current research addresses these issues: in CT, progress in reduction of ionizing radiation using iterative reconstruction [39, 40], visualization of vessel lumina along stents and calcifications [41, 42] and characterization of atherosclerotic plaques [43, 44] has been made. The development of free-breathing, ECG-triggered, navigator-gated, T2-prepared, 3-dimensional coronary MR angiography using steady state free precession (SSFP) sequence allows coronary imaging in MRI now, in principle without the need for contrast agents [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, both CT and MRI have drawbacks, like (high) doses of ionizing radiation, nephrotoxic contrast agents, impaired visualization of stenosis in stents and highly calcified vessels for CT and limited spatial and temporal resolution, limited patient access and restrictions for certain implants and medical devices for MRI. Current research addresses these issues: in CT, progress in reduction of ionizing radiation using iterative reconstruction [39, 40], visualization of vessel lumina along stents and calcifications [41, 42] and characterization of atherosclerotic plaques [43, 44] has been made. The development of free-breathing, ECG-triggered, navigator-gated, T2-prepared, 3-dimensional coronary MR angiography using steady state free precession (SSFP) sequence allows coronary imaging in MRI now, in principle without the need for contrast agents [45].…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage of this method is that there is a high likelihood of misregistration artefacts because the two breath-holding positions do not exactly match. Fuchs et al 15 reported that misregistration artefacts were seen in approximately half of the target segments in two breathhold subtraction CCTA. Third, the mean coronary calcium score in this study was only 898.…”
Section: Discussionmentioning
confidence: 99%
“…After performing subtraction using the contrast (a) and noncontrast image (b), a diagnostic image is obtained (c), which closely resembles the invasive coronary angiogram (d). [28,16]. Оценивали только сегменты с наличием выраженной кальцификации или наличием стентов.…”
Section: Figunclassified
“…Максимальное время задержки дыхания при этом составляло около 5-6 секунд. Но из-за разной глубины вдоха в ряде случаев происходило небольшое смещение анатомических структур друг относительно друга в разных наборах данных, что снижало точность выполнения дальнейшей субтракции [28,31,33].…”
unclassified